P PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR KOGNITIF SISWA: Pembelajaran - Alvandwi dwisaputra; Nurmitasari; Ferli Jeriyantoro; Amalia Ainaya Salsabilla; Wijayanti Wijayanti; Dina Bunga Lathifa (Jurnal Genta Mulia, 2026)
Cognitive learning outcomes in Natural and Social Sciences are still low in elementary schools due to teacher-centered instruction. This study aims to determine the effect of the Cooperative Integrated Reading And Composition model on the cognitive learning outcomes of fourth grade students. The research employed a quantitative approach with a quasi-experimental non equivalent control group design involving 20 students in the experimental class and 20 students in the control class. Data were obtained from a cognitive essay test administered after treatment. The normality test indicated a normal distribution with L count of the experimental class 2.461 and the control class 1.264, while the L table was 0.190. The homogeneity test showed homogeneous variance with F count 0.999 and F table 2.168. Hypothesis testing revealed a significant difference with a t count 7.20 and t table 1.686. The mean score of the experimental class was 76.6, higher than the control class 58.9. These findings indicate that the Cooperative Integrated Reading And Composition model has a positive effect on students’ cognitive learning outcomes.